“The Flower of Eastern and Western Europe” British Travellers, Czech Go-Betweens, and the Temporal Culture of Nineteenth-Century Prague - Hunter, Jana K. (Österreichische Zeitschrift für Geschichtswissenschaften, 2023)
Throughout the nineteenth century, published British travelogues revered Prague, bringing the city to the attention of the rest of Europe. Tropes and motifs predicated on German, Oriental, and classical imagery filled the pages of British travelogues, which were, in turn, entertained by Czech go-betweens in their own texts. This article explores the circulation of knowledge in compelling narratives between the travel writers and go-betweens who mapped out temporal representations of the city. A time-knowledge framework not only reveals how Prague’s temporal culture manifested itself in literary narratives and exchanges, but starts to rethink the development of the cultural, political, and social knowledge of the city, by demonstrating how different actors contributed to its production.